Serum Gamma-Glutamyltransferase Levels are Associated With Concomitant Cardiovascular Risk Factors in Korean Hypertensive Patients: A Nationwide Population-Based Study. Issue 50 (December 2015) - Lee, Sangsu; Kim, Do Hoon; Nam, Hyo Yun; Roh, Yong-Kyun; Ju, Sang-Yhun; Yoon, Yeo-Joon; Nam, Ga-Eun; Choi, Jun-Seok; Lee, Jong-Eun; Sang, Jung-Eun; Han, Kyungdo; Park, Yong-Gyu
Abstract : Abstract: Previous studies suggested that serum gamma-glutamyltransferase (GGT) levels were associated with the prevalence of cardiovascular disease (CVD) risk factors including hypertension, diabetes mellitus (DM), and metabolic syndrome (MetS) in the general population. We aimed to investigate the relationship between serum GGT levels and CVD risk factors in Korean hypertensive patients. This cross-sectional study was based on data from the Korea National Health and Nutrition Examination Survey (KNHANES) 2011 to 2012. The analysis included 1541 hypertensive participants. Study participants were divided into groups according to tertiles of serum GGT with cutoff points of 20 and 35 U/L. Serum GGT levels were positively associated with the components of MetS ( P value < 0.05, except for systolic blood pressure and high-density lipoprotein cholesterol). After adjusting for possible confounders, serum GGT levels were associated with an increased risk of MetS, high waist circumference, high triglyceride level, fasting plasma glucose, DM, and the urinary albumin-to-creatinine ratio ( P  = 0.001). In hypertensive patients, serum GGT levels are positively associated with major cardiovascular risk factors such as MetS, DM, and urinary albumin excretion.